ANALYSIS OF LANGUAGE STYLE IN POETRY "CINTA DALAM KEFANAAN" RUMI (A SEMIOTICS APPROACH) - Fitriyah, Fitriyah (Jurnal Ilmiah Bina Bahasa, 2021)
The aim of this research is to analyze one of Rumi's poetries entitled "Cinta dalam Kefanaan" which was translated by Abdul Hadi. Poetry will be analyzed based on a semiotic approach, which is to determine the style of language used in Rumi's poetry, especially the language that shows symbols of love. The poetry "Cinta dalam Kefanaan" is one of Rumi's poetry filled with the language of love. Rumi was completely immersed in his newfound love. The result shows that Rumi used a symbolic and romantic image of the search for a lost beloved. Love is made aware of the presence of the Master. Rumi's life story shows us that the longing and emptiness we feel because of losing love is a reflection of a longing for God, who is ultimately a manifestation of compassion found in his own soul.